Image of the city and modern architecture in the Polish feature films of the 1960s’ - Adam Nadolny (Images)
This article focuses on the inter-dependencies between the film image and architecture. The author has attempted to define what sort of historical background preconditions the film image to gain the status of a source for research on the history of Polish urban planning and post-war architecture, with particular emphasis placed on the 1960s.